2020
DOI: 10.7150/ijbs.45123
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on therapeutic neutralizing antibodies against the Novel Coronavirus SARS-CoV-2

Abstract: A newly identified novel coronavirus (SARS-CoV-2) is causing pneumonia-associated respiratory syndrome across the world. Epidemiology, genomics, and pathogenesis of the SARS-CoV-2 show high homology with that of SARS-CoV. Current efforts are focusing on development of specific antiviral drugs. Therapeutic neutralizing antibodies (NAbs) against SARS-CoV-2 will be greatly important therapeutic agents for the treatment of coronavirus disease 2019 . Herein, the host immune responses against SARS-CoV discussed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
248
1
21

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(274 citation statements)
references
References 58 publications
4
248
1
21
Order By: Relevance
“…Our previous studies revealed that the RBD site contains multiple groups of conformation-dependent neutralizing epitopes: some epitopes are critically involved in RBD binding to the cell receptor ACE2, whereas other epitopes possess neutralizing function but do not interfere with the RBD-ACE2 interaction ( 15, 18 ). Indeed, most of neutralizing monoclonal antibodies (mAbs) previously developed against SARS-CoV target the RBD epitopes, while a few are directed against the S2 subunit or the S1/S2 cleavage site ( 29, 30 ). The cross-reactivity of such mAbs with SARS-CoV-2 has been characterized, and it was found that many SARS-CoV-neutralizing mAbs exhibit no cross-neutralizing capacity ( 9, 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies revealed that the RBD site contains multiple groups of conformation-dependent neutralizing epitopes: some epitopes are critically involved in RBD binding to the cell receptor ACE2, whereas other epitopes possess neutralizing function but do not interfere with the RBD-ACE2 interaction ( 15, 18 ). Indeed, most of neutralizing monoclonal antibodies (mAbs) previously developed against SARS-CoV target the RBD epitopes, while a few are directed against the S2 subunit or the S1/S2 cleavage site ( 29, 30 ). The cross-reactivity of such mAbs with SARS-CoV-2 has been characterized, and it was found that many SARS-CoV-neutralizing mAbs exhibit no cross-neutralizing capacity ( 9, 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of memory cells is an important element to consider in the development of the anti-SARS-coV-2 vaccine (60). cases have been described where the SARS-coV-2 infection recurs after being considered cured (61).…”
Section: The Development Of a Covid-19 Vaccine: Current Trends And Prmentioning
confidence: 99%
“…In this special issue, we have 11 reports, which share our understanding of SARS-CoV-2 and COVID-19 from different angles. Zheng indicated that SARS-CoV-2 is an emerging new coronavirus that causes a global threat, and summarized the key events occurred during the early outbreak, the basic characteristics of the pathogen, the signs and symptoms of the infected patients, the possible transmission pathways of the virus, the Zhou and Zhao pointed out the great importance of using therapeutic neutralizing antibodies (NAbs) to control the spread and re-emergence of SARS-CoV-2 and assert that the development of NAbs therefore should be a high priority in near future [5]. Yang and Shen discussed the implication of the endocytic pathway and autophagy in viral infection and how novel therapeutic approaches could be developed by targeting these processes for treatment of COVID-19 [6].…”
mentioning
confidence: 99%